2004
DOI: 10.1159/000081628
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis on Factors Affecting Suppression of Thyroid-Stimulating Hormone in Treated Congenital Hypothyroidism

Abstract: Aims: To determine the factors which influence the suppression of thyroid-stimulating hormone (TSH) in infants with congenital hypothyroidism (CH) following treatment. Methods: We examined retrospectively the patterns of thyroid function tests from diagnosis to 3 years of age in 140 infants diagnosed with CH from screening. Patients were classified into 3 groups: athyreosis, ectopia and presumed dyshormonogenesis on the basis of thyroid scans. Adequate TSH suppression was defined as plasma TSH concentration <6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Thyroid ectopia has been the most common aetiology and dyshormonogenesis the least common aetiology in recent studies (7,9,10 This discrepancy may be due to differences in populations studied and different screening evaluations used. We have previously reported that aetiology of CH was an independent factor affecting suppression of TSH and there were distinct hormonal profiles in response to treatment according to aetiology of CH (11). Our present study shows that responsiveness to treatment with LT4 showed no difference between sexes in the different aetiological groups, as judged by age at suppression of plasma TSH.…”
Section: Discussionsupporting
confidence: 52%
“…Thyroid ectopia has been the most common aetiology and dyshormonogenesis the least common aetiology in recent studies (7,9,10 This discrepancy may be due to differences in populations studied and different screening evaluations used. We have previously reported that aetiology of CH was an independent factor affecting suppression of TSH and there were distinct hormonal profiles in response to treatment according to aetiology of CH (11). Our present study shows that responsiveness to treatment with LT4 showed no difference between sexes in the different aetiological groups, as judged by age at suppression of plasma TSH.…”
Section: Discussionsupporting
confidence: 52%
“…Neonatal screening of CH has proved effective in preventing mental retardation and growth failure. L -Thyroxine supplementation must be started immediately since the psychometric final outcome strongly depends on the earliness of the hormonal therapy [4, 5]. Because CH may be permanent or transient, especially if the thyroid is normally located and in premature births, imaging often plays an important role in avoiding unnecessarily long T 4 therapy in patients with transient diseases or in optimizing thyroxine supplementation in permanent cases [6].…”
Section: Introductionmentioning
confidence: 99%